The Use of Environmental Accounting to Determine Energy Saving in Mpumalanga Hotels, South Africa - Machete, F.; Hongoro, C.; Nhamo, G.; Mearns, K.F. (Journal of Environmental Accounting and Management, 2026)
This paper presents an energy characterisation framework that is based on environmental and carbon management accounting principles and practices that promote green growth in societies. Primary data was collected through survey questionnaires, observation checklists, energy account records, light meters and thermometers. In addition, an exploratory literature analysis was done. The collected data was analysed through descriptive and correlation statistics, aimed at testing the theoretically developed energy saving characterisation framework. The paper revealed that the use of one or two energy saving indicators as a base for characterising services and institutions as being energy saving is misleading. Thus, the paper concludes that energy saving characterisation should be based on a confirmed reduction of energy demand, cost and carbon footprint. However, the paper points out that the selection of energy saving technologies and characterisation of activities as energy saving method can be based on the ability of such an activity to reduce one or more of the three indicators. Ultimately, the adopted framework integrates environmental and carbon management accounting principles and practices.